Características comportamentais de suínos em crescimento e terminação em sistema wean to finish - Massari, Juliana M.; Curi, Thayla M. R. De C.; De Moura, Daniella J.; Medeiros, Brenda B.L.; Salgado, Douglas D'Alessandro [UNESP] (My University, 2015)
The wean to finish is a pig housing system, in which animals remains in the same building from the weaning to slaughter. The objective was to study the behavior of animals in unique accommodation of 26 male pigs (T1), mixed (T2), containing 13 males and 13 females, and the only treatment of females (T3) with 26 animals. For this, we used multivariate analysis, by analyzing the principal components, as an interesting tool used by many researchers to identify which variables are strongly correlated or not. Thus, we observed the main trends and characteristics in each treatment. The increase in air temperature has caused the behavior of lying down in every treatment. Only in the male treatment, the mount behavior is related to addiction, however in the mixed treatment the mount is related to a playful behavior. Only female pigs' treatment did not show any mount behavior.
Behavioral characteristics of different gender division of growing and finishing swine in wean to finish system
Keywords: Behavior; Livestock; Multivariate; Swine production; Welfare